A novel variant of PLA2G6 gene related early-onset parkinsonism: a case report and literature review - Cai, Dapeng; Wu, Haohao; Huang, Baogang; Xiao, Weiwei; Du, Kang (Frontiers in Neurology, 2024)
This study reported a case of early-onset parkinsonism associated with a novel variant of the PLA2G6 gene. The boy first started showing symptoms at the age of 11, with gait instability and frequent falls. As the disease progressed, his gait instability worsened, and he developed difficulties with swallowing and speaking, although there was no apparent decline in cognitive function. An MRI of the head revealed significant atrophy of the cerebellum. The initial diagnosis for the boy was early-onset parkinsonism, classified as Hoehn-Yahr grade 5.Genomic sequencing of the patient indicated that he had compound heterozygous variations in the PLA2G6 gene: c.1454G>A (p.Gly485Glu) and c.991G>T (p.Asp331Tyr). Pedigree analysis revealed that his younger brother also carried the same variant, albeit with milder symptoms. The patient's unaffected mother was found to be a carrier of the c.991G>T variant. Additionally, this study reviewed 62 unrelated families with PLA2G6 gene-related early-onset parkinsonism. The analysis showed a higher proportion of female probands, with a mean age of onset of ~23.0 years. Primary symptoms were predominantly bradykinesia and psychosis, with tremors being relatively rare. Cerebellar atrophy was observed in 41 patients (66.1%). Among the reported mutations, the most common mutation was c.991G>T, presenting in 21 families (33.9%), followed by c.2222G>A in eight families (12.9%). Other mutations were less common. Notably, the c.991G>T mutation was exclusive to Chinese families and was a prevalent mutation among this population. The initial symptoms varied significantly among patients with different mutations.